DEVELOPMENT OF VARIOUS MODERATION-ORIENTED COUNSELING A: CASE STUDY AT THE AJUNG RELIGIOUS AFFAIRS OFFICE, JEMBER - Abdul Halim; Lailatus Safitri, Novia; Riski Ramadhan (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study examines the implementation of religious moderation at the Ajung Jember Religious Affairs Office (KUA), using a qualitative approach with a case study type, data obtained through key informants, including the head of KUA, the religious section, and the community section. Data collection through in-depth interviews, observation, and documentation. The results of the study indicate that the Ajung Jember KUA has successfully utilized the Bimwin program to educate prospective brides and grooms about the importance of respecting differences in marriage. The religious counseling program also targets various levels of society to overcome radicalism and strengthen national values. However, this study also identified several challenges, including limited human resources and resistance from some people to the idea of religious moderation. Opportunities found in this study include increased public awareness of the importance of social harmony and the use of information technology to expand the reach of the program. This study contributes to the understanding of the implementation of religious moderation at the local level, with recommendations for strengthening human resource capacity and cross-sector collaboration in supporting the sustainability of religious moderation programs. Keywords: Religious moderation, KUA, Counseling.